TEKTONOSTRATIGRAFI DALAMAN BEREMBANG BAGIAN SELATAN - ADLAN , FITRA
The Southern Berembang Deep is the NE-SW trending of Jambi Sub-basin rift system and its bounded by normal fault zone, which define as classic half graben fault block. The polarity of the block-bounding faults changes along the axis of the rift, dividing the rift into two dip provinces, Rengancondong-Bunginbatu block (NE depocenter) and Malapari-Bulian block (SW depocenter). Rengancondong-Bunginbatu fault block has a NW dip, controlled on its eastern margin by Sangeti fault block. Otherwise, Malapari-Bulian fault block has a SE dip controlled on its western part by Tembesi fault block. The changes in polarity caused by transfer zone between these two fault block. Rifting in Southern Berembang Sub-basin took place during Oligocene until Early Miocene. Biostratigraphic investigations of several wells show that depositional environment at early stage synrift in this area began with marine (littoral), different from depostional environment at South Sumatra basin in general, where depositional environment began with non marine. Biostratigraphy analysis and sedimentary record (tectonostratigraphy) from this area show the time difference end of rifting stage in this two area (Rengancondong-Bunginbatu and Malapari-Bulian). The fault displacement of NE depocenter end much earlier (late Oligocene) than SW depocenter (early Miocene/N4).